The Development of Learning Activities on Living in Other Religions Using Board Games to Enhance the Academic Achievement of Mathayomsuksa 3 Students - Onrit, Suntorn; Matsimma, Marisa; Krutsri, Soodkhe (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This study aimed to: 1. develop lesson plans integrating board games into learning activities; 2. compare students' learning achievement before and after participating in these activities; and 3. assess students' satisfaction with the use of board games in the learning process. The sample consisted of 35 Mathayomsuksa 3 students (Grade 9), Class 3/2, at Tha Wung Witthayakarn School, Lopburi Province, during the first semester of the 2024 academic year, selected through cluster sampling. Research instruments included 15 lesson plans, a 30-item learning achievement test with a reliability coefficient of 0.85, and a 15-item satisfaction questionnaire with a reliability coefficient of 0.88. Data were analyzed using mean, standard deviation, and dependent t-test. The findings revealed that: 1. the development process produced 15 lesson plans, which were evaluated by experts as being at the highest quality level (M = 4.53, S.D. = 0.21); 2. students’ post-test scores (M = 20.50, S.D. = 0.85) were significantly higher than their pre-test scores (M = 11.50, S.D. = 0.70), with statistical significance at the 0.05 level; and 3. student satisfaction with the use of board games in learning was rated at the highest level (M = 4.52, S.D. = 0.60).